Enhanced Antimalarial Activity of Extracts of Artemisia annua L. Achieved with Aqueous Solutions of Salicylate Salts and Ionic Liquids - Ferreira, Ana M. (2024)
Artemisinin, a drug used to treat malaria, can be chemically synthesized or extracted from Artemisia annua L. However, the extraction method for artemisinin from biomass needs to be more sustainable while maintaining or enhancing its bioactivity. This work investigates the use of aqueous solutions of salts and ionic liquids with hydrotropic properties as alternative solvents for artemisinin extraction from Artemisia annua L. Among the investigated solvents, aqueous solutions of cholinium salicylate and sodium salicylate were found to be the most promising. To optimize the extraction process, a response surface method was further applied, in which the extraction time, hydrotrope concentration, and temperature were optimized. The optimized conditions resulted in extraction yields of up to 6.50 and 6.44 mg·g-1, obtained with aqueous solutions of sodium salicylate and cholinium salicylate, respectively. The extracts obtained were tested for their antimalarial activity, showing a higher efficacy against the Plasmodium falciparum strain compared with pure (synthetic) artemisinin or extracts obtained with conventional organic solvents. Characterization of the extracts revealed the presence of artemisinin together with other compounds, such as artemitin, chrysosplenol D, arteannuin B, and arteannuin J. These compounds act synergistically with artemisinin and enhance the antimalarial activity of the obtained extracts. Given the growing concern about artemisinin resistance, the results here obtained pave the way for the development of sustainable and biobased antimalarial drugs. © 2024 The Authors. Co-published by Zhejiang University and American Chemical Society.